2004
DOI: 10.1007/s00383-004-1297-1
|View full text |Cite
|
Sign up to set email alerts
|

Experience with anorectal malformations in Ile-Ife, Nigeria

Abstract: The study was carried out to determine the characteristics and outcome of management of anorectal malformations (ARM) in Nigerian children at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC) in Ile-Ife, Nigeria, between January 1986 and December 2002. Eighty-six children with ARM were studied, 48 males and 38 females. Only 12 (13.9%) presented to the hospital within 24 h of birth. Twenty-four (27.9%) patients had one or more associated congenital anomalies, with oesophageal atresia with trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 7 publications
4
38
0
3
Order By: Relevance
“…This type of surgery, especially in children with long common channels, represents one of the most challenging procedures that paediatric surgeons perform worldwide. [18] Others in the region have reported operating similar number of cases [13][14][15] of such severity. The challenge, however, is that operating on relatively small number of those cases may not allow individual surgeons to have adequate expertise that exposure to multiple cases of cloacal malformations or cloacal exstrophy will provide; hence, it may be worthwhile for centres to continue their efforts at collaboration [19] where surgeons in the sub-region often visit other centres when they have such cases and there may be a need to identify hospitals with greater resources to manage complex colorectal problems in children.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This type of surgery, especially in children with long common channels, represents one of the most challenging procedures that paediatric surgeons perform worldwide. [18] Others in the region have reported operating similar number of cases [13][14][15] of such severity. The challenge, however, is that operating on relatively small number of those cases may not allow individual surgeons to have adequate expertise that exposure to multiple cases of cloacal malformations or cloacal exstrophy will provide; hence, it may be worthwhile for centres to continue their efforts at collaboration [19] where surgeons in the sub-region often visit other centres when they have such cases and there may be a need to identify hospitals with greater resources to manage complex colorectal problems in children.…”
Section: Discussionmentioning
confidence: 95%
“…Delayed presentation is typical as reported from different centres in Nigeria. [13][14][15] The delay in presentation is often due to socioeconomic challenges, distance between place of residence and urban centres where paediatric surgical units are located [16] and poor awareness by mothers, [17] and perhaps health care workers [13] about the different spectrum of colorectal pathologies. The patients with HD particularly presented much later than those with anorectal malformations with only 18% of the patients operated on account of HD presenting with symptoms suggestive of the disease in the first 28 days of life.…”
Section: Discussionmentioning
confidence: 99%
“…A imperfuração anal é uma das anomalias anorretais e está associadas aos defeitos em outros sistemas do corpo (3,8) , e estudos mostram a associação mais frequente com o trato urogenital (9)(10)(11)(12)(13)(14) ; a sobrevida depende da severidade das anomalias associadas. Logo no início deve-se obter uma anamnese sistemática e iniciar o tratamento, cirúrgico ou clínico, o mais precoce possível, a lesão se desenvolve devido à falta de complementação do complexo embriológico (15)(16)(17)(18)(19) . O tratamento cirúrgico convencional é a confecção da colostomia pélvico proximal (20)(21) , em neonatos com um dia de vida, seguindo a formação da fístula com a realização da anorretoplastia sagital posterior, realizada aos 4 ou 6 meses de vida (22)(23) .…”
Section: Resul Resul Resul Resul Results T T T Tado Ado Ado Ado Ados Sunclassified
“…Mortality related to ARM is still high in Africa (30.5%) because most patients are referred late for medical attention. Adejuyigbe et al, [4] reports that only 15% are observed within 24 hours of life. Male infants present vomiting and progressive abdominal distension and are destined to die whenever colostomy is not performed on emergency basis.…”
Section: Discussionmentioning
confidence: 97%